Media informasi dan tingkat pendidikan berhubungan dengan kehamilan remaja Indonesia - Ayu Aminatussyadiah; Suci Fitriana Pramudya Wardani; Amrina Nur Rohmah (Universitas Muhammadiyah Semarang, 2020)
In the digital era, everyone has free access to various content using an electronic device, including teenagers. Pornographic content is also easy to access. The lack of reproductive knowledge among teenagers can cause risk behavior such as unsafe sexual activity that can lead to teenage pregnancy. Teenage pregnancy is a serious problem that can be endangering every young mother’s life. This condition can be a life-threatening for both mother and baby. This study aimed to determine the effect of media access and adolescent girls' educational levels on the incidence of teenage pregnancy in Indonesia. A cross-sectional design was used in this study. This study's sample was all young women contained in the 2012 IDHS data with an age range of 15-19 years old with a total sample size of 7,203 respondents. A Chi-square test was used in this study for data analysis. The results of this study show that there is a relationship between media information and the educational level of adolescent girls to the incident of teenage pregnancy in Indonesia.